LOS ESTUDIOS DE OPINIÓN - Ruiz Restrepo, Jaime (La Sociología en sus Escenarios, 2010)
Abstract. The public opinion studies could be defined as: "The determination than people wants, by methods of formation of samples selective" (Lundberg). The ample field of the opinions, the feelings and the expectations, has been constituted in excellent broth of culture for "specialists in predictions". The opinion studies show the ample field of the opinions, of the feelings and of the expectations and, they have constituted themselves in excellent broth of culture for "specialists in predictions". The instrument of information harvesting is the survey that is a technique destined to obtain primary data of a representative number of individuals of a population to project its results on the total population. Problems: The problem is that the drilled people finish expressing not their preference, but the idea that forms of the opinions of the others. The surveys confuse popularity with credibility" The surveys let see what is what they want to hear the voters and what it is what they hope of the candidates. By this route the candidate makes his speech and its image is handled, inducing to the electorate. And additionally we add like negative aspect, that those people can be lead in partisan attitude, under studies "manipulated", bringing about consequently a greater disorientation: "The problem is in which all the soundings have not been made seriously. In some notes that are too much is committed. Sometimes it has been incurred twisted manipulations and the results have left slanted Resumen. Los estudios de opinión pública muestran el amplio campo de las opiniones, de los sentimientos y de las expectativas y, se han constituido en excelente caldo de cultivo para los "especialistas en predicciones". El instrumento de recolección de información es la encuesta que es una técnica destinada a obtener información primaria de un número representativo de individuos de una población para proyectar sus resultados sobre la población total. Dificultades: El problema es que las personas sondeadas acaban por expresar no su preferencia, sino la idea que se forman de las opiniones de los demás. Las encuestas confunden popularidad con credibilidad." Las encuestas dejan ver qué es lo que quieren oír los electores y qué es lo que esperan de los candidatos. Por esta vía el candidato elabora su discurso y se maneja su imagen, induciendo al electorado. Y adicionalmente agreguemos como aspecto negativo, que esas personas pueden ser conducidas en actitud proselitista, bajo estudios "amañados", provocándose en consecuencia una mayor desorientación: "El problema está en que no todos los sondeos se han hecho con seriedad. En algunos se nota que están demasiado comprometidos. A veces se ha incurrido en torcidas manipulaciones y los resultados han salido sesgados